The business model Canvas with Al-Izhar High School and IPMI Institute - Samuel P. D. Anantadjaya (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
On June 13, 2025, Al-Izhar High School collaborated with IPMI International Business School in a dynamic learning program centered on the Business Model Canvas (BMC). The initiative was designed to introduce high school students to the fundamental concepts of entrepreneurship and business strategy through experiential learning. By engaging directly with the BMC framework, students explored the nine key building blocks, including value propositions, customer segments, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure, and applied these concepts to real or simulated business ideas. This collaboration provided Al-Izhar students with a unique opportunity to connect classroom knowledge with practical applications, enhancing their analytical and creative problem-solving abilities. Guided by IPMI faculty and student mentors, participants worked in teams to design business models, present their findings, and receive constructive feedback. The program not only strengthened students’ understanding of innovation and entrepreneurship but also encouraged teamwork, adaptability, and leadership skills. For the IPMI Institute, the activity demonstrated its commitment to shaping future leaders and fostering entrepreneurial mindsets at an early stage. Overall, the partnership underscored the importance of integrating higher education expertise into secondary education to empower students with future-ready skills.   Abstrak Pada 13 Juni 2025, SMA Al-Izhar berkolaborasi dengan IPMI International Business School dalam program pembelajaran dinamis yang berpusat pada Business Model Canvas (BMC). Inisiatif ini dirancang untuk memperkenalkan murid SMA pada konsep-konsep dasar kewirausahaan dan strategi bisnis melalui pembelajaran berbasis pengalaman. Dengan terlibat langsung dengan kerangka kerja BMC, murid mengeksplorasi sembilan blok bangunan utama yang meliputi proposisi nilai, segmen pelanggan, saluran, hubungan pelanggan, aliran pendapatan, sumber daya utama, aktivitas utama, kemitraan utama, dan struktur biaya, sambil menerapkannya pada ide bisnis nyata maupun simulasi. Kolaborasi ini memberikan murid Al-Izhar kesempatan unik untuk menghubungkan pengetahuan di kelas dengan aplikasi praktis, meningkatkan kemampuan analitis dan pemecahan masalah kreatif mereka. Dibimbing oleh fakultas dan mentor murid IPMI, para peserta bekerja dalam tim untuk merancang model bisnis, mempresentasikan temuan mereka, dan menerima umpan balik yang konstruktif. Program ini tidak hanya memperkuat pemahaman murid tentang inovasi dan kewirausahaan, tetapi juga mendorong kerja sama tim, kemampuan beradaptasi, dan keterampilan kepemimpinan. Bagi Institut IPMI, kegiatan ini menunjukkan komitmennya untuk membentuk pemimpin masa depan dan menumbuhkan pola pikir kewirausahaan sejak dini. Secara keseluruhan, kemitraan ini menggarisbawahi pentingnya mengintegrasikan keahlian pendidikan tinggi ke dalam pendidikan menengah untuk memberdayakan murid dengan keterampilan siap masa depan. Kata Kunci: BMC; keterampilan pengetahuan; kewirausahaan dasar; komunikasi; pengembangan ide bisnis dunia nyata